THE EFFECT OF FINANCIAL, NON-FINANCIAL INFORMATION, AND ECONOMIC CONDITION ON THE LEVEL PRIME SHARE MISPRICING - Albert Nanda Saputra; Tri Joko Prasetyo; Dewi Sukmasari (TECHNOBIZ : International Journal of Business, 2023)
Amid the recovery in world economic conditions due to the Covid-19 pandemic, companies are trying to make various efforts to obtain additional capital for the company's sustainability; where one of these efforts is by conducting an Initial Public Offering. A phenomenon occurs when a company conducts an IPO, namely initial public offering mispricing, which can be detrimental to investors and the company, so research is needed on what factors can influence initial public offering mispricing. This study aims to see whether profitability, leverage, percentage of public shares, the purpose of using IPO funds, inflation, and economic growth affect the level of initial public offering mispricing. This study's secondary data is obtained from prospectus reports for IPO companies on the Indonesia Stock Exchange (IDX) for 2010-2021. The analysis technique used in this study is descriptive statistics, classical assumption testing, and multiple linear regression, with the analytical tool used as SPSS 26. The results show that profitability, leverage, percentage of public shares, and inflation significantly affect the level of initial public offering mispricing. At the same time, the purpose of using IPO funds and economic growth had little effect on the level of initial public offering mispricing.